ANALISIS KEMAMPUAN MAHASISWA MERANCANG PEMBELAJARAN SASTRA INDONESIA PADA MATA KULIAH TEORI DAN PRAKTIK PENGAJARAN SASTRA INDONESIA - Tri Astuti; Dwi Desi Fajarsari; Ajeng Tina Mulyana (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT The ability to design literature instruction is a crucial competency for prospective Indonesian language and literature teachers, given that literature instruction emphasizes appreciation, expression, and the internalization of values. This study addresses the gap between students' conceptual mastery of literature teaching theories and their practical ability to design literature lessons suitable for the classroom. The study aims to describe and analyze students' abilities in designing Indonesian literature lessons within the "Theory and Practice of Indonesian Literature Teaching" course, specifically regarding the formulation of learning objectives, selection of teaching materials, use of teaching methods and strategies, and design of assessments for literary appreciation. A quantitative descriptive approach was employed, involving 40 students from the Indonesian Language and Literature Education program at Universitas Indraprasta PGRI, selected via purposive sampling. Data were collected through a performance test—specifically the creation of a literature lesson plan—evaluated using a rubric and analyzed using descriptive percentage statistics. The results indicate that the students' overall ability fell into the "good" category, with a breakdown of 15% in the "very good" category, 45% in "good," 30% in "fair," and 10% in "poor." The highest achievement levels were observed in the formulation of learning objectives and the selection of teaching materials, while the lowest levels were found in the design of literary appreciation assessment instruments and the selection of varied teaching methods. The study concludes that practical application, teaching simulations, and literature-focused microteaching activities need to be enhanced to optimize students' readiness to design and implement literature instruction in schools. ABSTRAK Kemampuan merancang pembelajaran sastra merupakan kompetensi penting yang harus dimiliki mahasiswa calon guru bahasa dan sastra Indonesia karena pembelajaran sastra memiliki karakteristik yang menekankan aspek apresiasi, ekspresi, dan penghayatan nilai. Permasalahan yang melatarbelakangi penelitian ini adalah adanya kesenjangan antara penguasaan teori pengajaran sastra secara konseptual dengan kemampuan mahasiswa dalam menyusun rancangan pembelajaran sastra yang aplikatif di kelas. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis kemampuan mahasiswa dalam merancang pembelajaran sastra Indonesia pada mata kuliah Teori dan Praktik Pengajaran Sastra Indonesia, meliputi perumusan tujuan pembelajaran, pemilihan bahan ajar, penggunaan metode dan strategi pembelajaran, serta perancangan penilaian apresiasi sastra. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan subjek penelitian sebanyak 40 mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Indraprasta PGRI menggunakan teknik purposive sampling . Data dikumpulkan melalui tes kinerja berupa penyusunan rancangan pembelajaran sastra yang dinilai menggunakan rubrik penilaian, kemudian dianalisis secara deskriptif persentase. Hasil penelitian menunjukkan bahwa kemampuan mahasiswa secara umum berada pada kategori baik, dengan rincian 15% kategori sangat baik, 45% kategori baik, 30% kategori cukup, dan 10% kategori kurang. Aspek dengan capaian tertinggi terdapat pada perumusan tujuan pembelajaran dan pemilihan bahan ajar, sedangkan aspek terendah terdapat pada perancangan instrumen penilaian apresiasi sastra dan pemilihan metode pembelajaran yang variatif. Penelitian ini menyimpulkan bahwa penguatan praktik, simulasi mengajar, dan kegiatan microteaching sastra perlu ditingkatkan untuk mengoptimalkan kesiapan mahasiswa dalam merancang dan melaksanakan pembelajaran sastra di sekolah.